The Implementation of “Journalists’ Questions” in Teaching Writing to the Eighth Graders of SMPN 2 Tanggul (RETAIN, 2016)
The Implementation of “Journalists’ Questions” in Teaching Writing to the Eighth Graders of SMPN 2 Tanggul Muhammad Naufal Zulkarnain English Education Study Program, Faculty Languages and Arts, The State University of Surabaya m.zulkarnain@mhs.unesa.ac.id Dr. Oikurema Purwati, M.A., M.Appl. English Education Study Program, Faculty Languages and Arts, The State University of Surabaya pungki_unesa@yahoo.co.id Abstrak Bahasa Inggris adalah bahasa yang dapat dengan mudah diintregasikan kepada setiap aspek kehidupan manusia. Lagipula, penggunaan bahasa Inggris sebagai bahasa kedua di Indonesia menuntut siswa untuk menguasai bahasa Inggris baik lisan maupun tulisan. Dalam pembelajaran bahasa Inggris, kemampuan menulis tidak bisa didapatkan secara instan. Maka dari itu untuk menjadi penulis yang baik membutuhkan latihan yang lebih. Journalists’ questions adalah sebuah teknik yang dapat menjadi alternatif untuk membantu siswa dalam penulisan. Menjadi bukti bahwa teknik journalists’ questions tidak hanya memberikan petunjuk untuk siswa dalam penulisan teks, tetapi juga menghubungkan pengalaman mereka ketika mengumpulkan ide. Dan lagi, teknik ini juga menggambarkan tugas yang nyata dimana siswa dituntut untuk mengumpulkan informasi dari berbagai sumber dengan menggunakan naluri penemuannya. Penelitian ini dilaksanakan menggunakan deskriptif kualitatif. Data dikumpulkan menggunakan beberapa instrumen seperti field note, document review, dan interview. Lalu, sebagai pokok penelitian adalah siswa kelas VIII G SMPN 2 Tanggul. Sementara itu, Hasil dari penelitian ini menunjukkan bahwa teknik journalists’ questions telah dilakukan dengan baik. Pertanyaan yang disajikan dalam teknik membantu siswa dalam mengorganisir ide untuk mengumpulkan dan mengembangkannya dalam tulisan. Dapat disimpulkan bahwa pengimplementasian teknik journalists’ questions sangat bermanfaat untuk dicoba dalam pengajaran penulisan. Terutama dalam pengajaran penulisan teks recount. Kata Kunci: implementasi, journalists’ questions, menulis, teks recount. Abstract English is a language which can easily be integrated into every field of peoples’ life. Moreover, the use of English as second language in Indonesia may affect students to have ability to master English both oral and written. In teaching English, writing skill can’t be achieved instantly so that become a good writer need more practice. Journalists’ questions technique can be alternative technique to assist students’ writing. It is evident that journalists’ questions technique not only provides clues for students to compose the text, but also connects their life time experience in generating their ideas. In addition, the technique also reflects real-life task where the students have to gather the information from various sources using their discovery instinct. This study is conducted as descriptive qualitative research. The data obtained by using the following instruments such as field note, documents review, and interview. Thus, the subjects of this study are students and the English teacher of VIII-G SMPN 2 Tanggul. Meanwhile, the result showed that journalists’ questions technique was conducted properly. Questions provided in the journalists’ questions guide the students to organize students’ idea in gathering and developing their writing. It then briefly examines that the implementation of journalists’ questions technique is worth to try to teach writing, especially for teaching students’ writing recount text. Keywords: implementation, journalists’ questions, writing, recount text.